1970
DOI: 10.1007/bf01378230
|View full text |Cite
|
Sign up to set email alerts
|

The composition of the leachate through cropped and uncropped soils in lysimeters compared with that of the rain

Abstract: SUMMARYThe composition of the leachate from undisturbed monolith lysimeters cropped with white clover or meadow fescue or maintained bare was compared with t h a t of the rain falling on rhein. No nitrogen fertilizer was applied only an initial dressing of phosphorus and potassium. The grass received rauch more nitrogen from the rain than it lost by leaching whereas the clover lost more t h a n it received. Most of the leached Ilitrogen was N O s -N -92 per cent on the bare soil and 90 per cent on the clover. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
4

Year Published

1975
1975
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 10 publications
0
16
1
4
Order By: Relevance
“…However, under pasture, leaching losses of soil N (Table 1) are considerably higher than those reported in the literature. This is in contrast to earlier conclusions based on results from monolith and filled-in lysimeter studies (Karraker et al 1950;Theron 1964;Low & Armitage 1970) and periodical analyses of inorganic N levels at various soil depths (Cunningham & Cooke 1958;Gasser 1959;Tham 1971;Risk 1976).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, under pasture, leaching losses of soil N (Table 1) are considerably higher than those reported in the literature. This is in contrast to earlier conclusions based on results from monolith and filled-in lysimeter studies (Karraker et al 1950;Theron 1964;Low & Armitage 1970) and periodical analyses of inorganic N levels at various soil depths (Cunningham & Cooke 1958;Gasser 1959;Tham 1971;Risk 1976).…”
Section: Discussioncontrasting
confidence: 82%
“…These lysimeters have larger cross-sectional areas than porous tubes or cups and therefore they are more likely to reduce sampling errors, especially in the composition of the leachate collected (van der Ploeg & Besse 1977). Furthermore, the installation of tension lysimeters causes little distortion of soil structure and the plant rooting system compared with installing various kinds of classical lysimeters, whose relative merits have been discussed extensively by Low & Armitage (1970).…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding figures in the grass-clover sward were 16.7 (1 st year), 19.8 (2 nd year) and 21.0 (3 rd year) mg L -1 N, and in the grass-only sward 15.9 (1 st year), 17.5 (2 nd year) and 19.7 (3 rd year) mg L -1 N. Significant difference between two swards appeared in the second year; probably it was due to the decrease in legume content in the sward (Table 5) and the decomposition of N-rich plant residues in the soil. Earlier Low and Armitage (1970) studies have demonstrated increased leaching in the swards with reduced legume content.…”
Section: Resultsmentioning
confidence: 87%
“…Eriksen et al (2004) have reported that less leaching occurs from unfertilized grassland containing white clover than from fertilized grass-only grassland. Low and Armitage (1970) studies have demonstrated increased leaching in the swards with reduced legume content.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen concentration of rainfall varies widely but is generally between 1 to 2.5 ppm (Low and Armitage, 1970). As it becomes available during the season (unlike fertilizer nitrogen which is immediately available at the beginning) it may -·· bSl_of cQnsiderikblej:rnp_ortancejn maintaining_ growth towards th~e_e,._,n""'d~o""'f"'----"t~h~e _____ _ season.…”
Section: B) Effect Of Rain-bo'j'ne Nitmgen On Productionmentioning
confidence: 99%